Evaluation of Stress Patterns Produced by Implant-Retained Overdentures and Implant-Retained Fixed Partial Denture - Mazaro, José Vitor Quinelli [UNESP]; Gennari Filho, Humberto [UNESP]; Vedovatto, Eduardo [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP]; Zavanelli, Adriana Cristina [UNESP] (Lippincott Williams & Wilkins, 2011)
The purposes of this study were to photoelastically measure the biomechanical behavior of 4 implants retaining different cantilevered bar mandibular overdenture designs and to compare a fixed partial denture (FPD). A photoelastic model of a human edentulous mandible was fabricated, which contained 4 screw-type implants (3.75 x 10 mm) embedded in the parasymphyseal area. An FPD and 3 overdenture designs with the following attachments were evaluated: 3 plastic Hader clips, 1 Hader clip with 2 posterior resilient cap attachments, and 3 ball/O-ring attachments. Vertical occlusal forces of 100 N were applied between the central incisor and unilaterally to the right and left second premolars and second molars. Stresses that developed in the supporting structure were monitored photoelastically and recorded photographically. The results showed that the anterior loading, the overdenture with 3 plastic Hader clips, displayed the largest stress concentration at the medium implant. With premolar loading, the FPD and overdenture with 3 plastic Hader clips displayed the highest stresses to the ipsilateral terminal implant. With molar loading, the overdenture with 3 ball/O-ring attachments displayed the most uniform stress distribution in the posterior edentulous ridge, with less overloading in the terminal implant. It was concluded that vertical forces applied to the bar-clip overdenture and FPD created immediate stress patterns of greater magnitude and concentration on the ipsilateral implants, whereas the ball/O-ring attachments transferred minimal stress to the implants. The increased cantilever in the FPD caused the highest stresses to the terminal implant.
Keywords: Dental implants; implant-supported dental prosthesis; dental stress analysis